PEMAKNAAN LABA (STUDI FENOMENOLOGI BAGI PELAKU USAHA MAKANAN) (Magister Manajemen Universitas Wisnuwardhana, 2022)
This study intends to find out how the meaning of profit for MSME entrepreneurs. This is due to the lack of knowledge of entrepreneurs in recording to find out the profits obtained in their business activities. The perception of profit according to them is how their business continues to run and can be used again for further capital. Through this research, it is expected to find a suitable concept in applying accounting science, especially in determining profit. This research is a qualitative research that reveals a unique meaning of accounting as understood by MSME entrepreneurs. Therefore, it is necessary to deepen the entity by using the phenomenological qualitative research method. Based on the results of the research conducted, that MSME entrepreneurs actually already understand the importance of an accounting practice in determining the profit from their business activities. This is evidenced by collecting evidence of business transactions and making small notes during the business as well as how to determine the profit in each transaction. In addition, they consider the benefits not only material but there are non-material benefits that they get. However, farmers have difficulty in compiling a good and correct financial report so that they never know how much profit for sure in each planting period. This is due to the lack of knowledge of good and correct accounting practices according to applicable standards. The recording carried out by the entrepreneur is only limited to a